Measurement of the differential cross sections of natLi(d,d0) for EBS purposes - Ntemou, E.; Preketes-Sigalas, K.; Aslanoglou, X.; Foteinou, V.; Kokkoris, M.; Lagoyannis, A.; Misaelides, P.; Patronis, N.; Provatas, G.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
In the present work, the 6,7Li(d,d0)6,7Li elastic scattering differential cross sections were measured in the energy range Elab = 900 – 2000 keV for EBS purposes, using thin lithium targets, made by evaporating natLiF and isotopically enriched 6LiF powder on self-supporting carbon stripping foils, with an ultra-thin Au layer on top for charge normalization purposes. The experiment was carried out in deuteron beam energy steps of 5 to 30 keV, depending on the fine structure of each studied cross section, and for the laboratory scattering angles of 125˚, 140˚, 150˚, 160˚, and 170˚.